2007
DOI: 10.1086/513018
|View full text |Cite
|
Sign up to set email alerts
|

A Debris Disk around the Central Star of the Helix Nebula?

Abstract: Excess emission from a pointlike source coincident with the central star of the Helix Nebula is detected with Spitzer at 8, 24, and 70 mm. At 24 mm, the central source is superposed on an extended diffuse emission region. While the [O iv] 25.89 mm line contributes to the diffuse emission, a 10-35 mm spectrum of the central source shows a strong thermal continuum. The excess emission from the star most likely originates from a dust disk with blackbody temperatures of 90-130 K. Assuming a simple optically thin d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 35 publications
7
142
0
Order By: Relevance
“…We determined an average dust temperature of 30.8 K ± 1.4. We detected the central star disk at 70 µm, confirming the result of Su et al (2007). At other Herschel wavelengths we only have upper limits, hence the dust temperature of the disk of 65 K is only an estimate.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We determined an average dust temperature of 30.8 K ± 1.4. We detected the central star disk at 70 µm, confirming the result of Su et al (2007). At other Herschel wavelengths we only have upper limits, hence the dust temperature of the disk of 65 K is only an estimate.…”
Section: Resultssupporting
confidence: 87%
“…The white dwarf central star WD 2226-210 with a surface temperature of 103 600 ± 5500 K (Napiwotzki 1999) ionizes the asymptotic giant branch (AGB) nebula. Su et al (2007) also showed the presence of a 35-150 AU diameter debris disk around this central star.…”
Section: Introductionmentioning
confidence: 78%
“…They are interpreted as circumbinary disks that formed during the mass-loss phase, or as debris disks either left over from the main sequence phase or built recently from tidally disrupted smaller orbiting bodies as discussed in e.g., Su et al (2007) or Brinkworth et al (2009). The plethora of different classes of objects with these disks (B[e] stars, symbiotic stars, RV Tau stars) indicates that they form relatively easily.…”
Section: Evolution Of the Diskmentioning
confidence: 99%
“…These disks are very different in nature from the one detected in the Hellix nebula (Su et al 2007). In the Hellix the disk is probably the final evolution of the Solar System Kuiper/belt analogue (see e. g. Bonson & Wyatt 2010).…”
Section: White Dwarfsmentioning
confidence: 65%